Restauração ecológica com uso de poleiros artificiais em área dominada por braquiária (Urochloa humidicola (Rendle) Morrone & Zuloaga). - Silva, João Carlos Barbosa da (2011)
To evaluate the restoration process in old fields, we use artificial perches with monthly evaluations during a year of seed rain, germination and plant establishment. Since the study area is dominated by exotic grass Urochloa humidicola (Rendle) Morrone & Zuloaga, he following hypotheses were tested (i) the presence of exotic grass prevents germination and establishment the other plants (ii) artificial perches increase germination and establishment consequently by increase seed rain. In the artificial perches was observed 36 birds species, mostly insectivorous birds, but sometimes can eat some fruits. Over the seed traps were collected 155 fecal samples, of which 10059 were removed seeds from 10 species and six morphospecies, with a clear dominance of Cecropia pachystachya Trec. Most species of plants that was present as the zoochory dispersion syndrome and early successional stage. Mostly of the seeds were zoochorous plants and were earlier successional stages.The species that germinated and became established during the evaluation period were mainly herbaceous and shrubs, with little contribution of trees and lianas. Among germinated plants were registered 24 species, representing 11 families with dominance of four species: Chamaecrista rotundifolia Greene., Sida cordifolia L., Sida rhombifolia L. e Solanum palinacanthum Dunal. The coverage by the exotic grass Urochloa humidicula limited the germination and establishment in the area, preventing the start on natural succession of the area.